Potassium forms distribution in soil as a result of lime application - Kaseker, Jéssica Fernandes; Ernani, Paulo Roberto; Almeida, Jaime Antonio de; Gerber, Jaqueline Muniz; Rosa, Eliete de Fátima Ferreira da (Revista de Ciências Agroveterinárias, 2022)
All forms of potassium in the soil are in a dynamic equilibrium with K in the soil solution, which affects K availability to the plants and it is affected by the soil pH. The objective of this study was to evaluate the effect of the soil pH and K application on the distribution of soil K forms in five Brazilian soils. The experiment was conducted in laboratory, using five soils. Treatments consisted of a factorial combination including rates of limestone (0, 0.25, 0.5, 1.0 and 1.5 times the amount of lime indicated by the SMP method to raise soil pH to 6.0) and two rates of K (0 and 1000 mg kg-1). Addition of KCl, together with limestone, promoted lower values of soil pH relatively to limestone alone. Solution K was the most sensitive K form affected by liming rates, which decreased in all soils with increases on K rate, regardless of K addition. Exchangeable K also decreased in all soils with the increase on lime applied, except on the Argisol. The non-exchangeable K levels were the least affected by liming. Addition of lime affects the distribution of K among all K forms and this may affect the availability of K to the plants.